Listening at Lookout Creek : Nature in Spiritual Practice - Van Wieren, Gretel (Book collections on Project MUSE., 2019)
"Gretel Van Wieren's family cabin, the Cedar Shack, in northwest Michigan's Manistee National Forest, is where she learned to fish and wade in rivers, build fires, send smoke signals, and distinguish false from true morels. It's where she came to love the water and woods, and where she is now trying to teach her children to do the same. But decades of moving from place to place-from Eastern Africa to New England-have made trips back to the Cedar Shack scarce and short-lived. Even after moving back to Michigan, Van Wieren and her husband's obligations as university professors and parents of three overscheduled teenagers have made forest time thin and rushed. It wasn't always like this. For years, Van Wieren studied and attempted to emulate the lives of the mystics. As a pastor in rural, dairy-farming New York, she walked the fields and woods behind the parsonage daily. Remembering that time in her life, Van Wieren concludes that she is out of practice, and she goes to the H.J. Andrews Experimental Forest in Oregon's western Cascade Mountains to conduct a spiritual experiment: Is it possible to rediscover a deep sense of connection with the natural world, and can it be done, with children, in today's high-tech, hyper-busy world? Listening at Lookout Creek weaves philosophical and spiritual interpretations of the natural world with personal, hands-on experiences of particular landed places"--